temporal paradox and its connotations in novels Hassan Hamid(Madinatu Allah, Kunt Hunak, Kraki) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research addresses the concept of temporal paradox theory and application, which is manifested in two basic forms: retrieval and anticipation, as instruments used by the novelist in order to create a monotonous and consistent sequence of narrative discourse, and not to subject the course of events in the novel to a single sequence of time , the retrieval was the path adopted by the novelist in returning to the heritage of the text and bringing it into the anchoring of the narrative construction of the novel. At the other end, anticipation was the author's approach to jumping into narrative time to anticipate the future of characters and events in order to prepare for or announce the event in the recipient's imagination.